Simulasi Molecular Docking Aktivitas Antiinflamasi Rimpang Zingiber Officinale var. amarum pada Mediator Inflamasi Prostaglandin D2 (PGD2) dan Tromboksan A2 (TXA2) pada Osteoarthritis - Denis Mery Mirza; Erna Sulistyowati; Anta Maulana Fardhani (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2024)
Abstract. Osteoarthritis (OA) is a degenerative joint disease characterized by damage to joint cartilage, subchondral bone, and osteophyte formation. The prevalence of OA is still large with major therapy is non steroid anti inflammatori (NSAID) drug. However, prolonged use of NSAIDs leads to side effects on gastrointestinal tract. Zingiber officinale var. amarum is beneficial herbal for anti-inflammatory therapy in OA. The damage of chondrocytes in OA triggers the activation of inflammatory process through the COX-2 pathway, resulting in the production of chemical mediators prostaglandin D2 (PGD2) and thromboxane A2 (TXA2), causing pain and functional decline. Thus, this research aimed to predict active compounds of Z. officinale var. amarum rhizomes that potential to inhibit PGD2 and TXA2 as anti-inflammatory agents for OA through molecular docking. Method This research use 20 active compounds of Z. officinale var. amarum using molecular docking method with proteins target including of PGD2 (ID:1S2A) and TXA2 (ID:6IIV). The docking process was conducted using the PyRX 0.8 application, and the results were visualized in the BIOVIA Discovery Studio 2020 application. Result the research on the 20 active compounds in the rhizome of Z. officinale var. amarum indicates that compounds such as [6]-Gingerdiol 3,5-diacetate, 10-gingerol, gingerdione, and gingerdiol can interact with the active site of the protein 1S2A through hydrogen bonding with Gln-222. Furthermore, compounds like [6]- dehydrogingerdione, paradol, gingerdiol, geraniol, 10-gingerol, gingerdione, [6]- Gingerdiol 3,5-diacetate, isoborneol, zingerone have been identified to interact with 6IIV through hydrogen bonding with Gln-301 and Thr-81. This indicates that these compounds exhibit activity as inhibitors of PGD2 and TXA2. The interactions occurring between the complex compounds of Z. officinale var. amarum and 1S2A and 6IIV can lead to inhibitory effects on PGD2 and TXA2. Kata Kunci: molecular docking; osteoarthritis; PGD2; TXA2; Z. officinale var. amarum